A Tiered Approach to Evaluating Salinity Sources in Water at Oil and Gas Production Sites. Issue 5 (25th April 2017) - Paquette, Shawn M.; Molofsky, Lisa J.; Connor, John A.; Walker, Kenneth L.; Hopkins, Harley; Chakraborty, Ayan
Abstract: A suspected increase in the salinity of fresh water resources can trigger a site investigation to identify the source(s) of salinity and the extent of any impacts. These investigations can be complicated by the presence of naturally elevated total dissolved solids or chlorides concentrations, multiple potential sources of salinity, and incomplete data and information on both naturally occurring conditions and the characteristics of potential sources. As a result, data evaluation techniques that are effective at one site may not be effective at another. In order to match the complexity of the evaluation effort to the complexity of the specific site, this paper presents a strategic tiered approach that utilizes established techniques for evaluating and identifying the source(s) of salinity in an efficient step‐by‐step manner. The tiered approach includes: (1) a simple screening process to evaluate whether an impact has occurred and if the source is readily apparent; (2) basic geochemical characterization of the impacted water resource(s) and potential salinity sources coupled with simple visual and statistical data evaluation methods to determine the source(s); and (3) advanced laboratory analyses (e.g., isotopes) and data evaluation methods to identify the source(s) and the extent of salinity impacts where it was not otherwise conclusive. A case study from the U.S. Gulf Coast is presented to illustrate the application of this tiered approach. Abstract : Article Impact Statement : A tiered approach is presented to identify the source of salinity in water using step‐by‐step data analysis and evaluation methods.